2022
DOI: 10.3390/jpm12091515
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Target Mechanisms of Phytochemicals in Alzheimer’s Disease: Effects on Oxidative Stress, Neuroinflammation and Protein Aggregation

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disease characterized by a tangle-shaped accumulation of beta-amyloid peptide fragments and Tau protein in brain neurons. The pathophysiological mechanism involves the presence of Aβ-amyloid peptide, Tau protein, oxidative stress, and an exacerbated neuro-inflammatory response. This review aims to offer an updated compendium of the most recent and promising advances in AD treatment through the administration of phytochemicals. The literature survey was carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 219 publications
0
17
0
Order By: Relevance
“…MAPKs are involved in the phosphorylation of JNK, ERK and p38 which regulate the expression of MSK 1/2 and then p65 ( Xie et al, 2019 ; Garzoli et al, 2022 ; Li et al, 2023 ). Inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) are also key enzymes involved in inflammation and cell stress, being NO an important regulator of COX-2 expression and activity ( Sharifi-Rad et al, 2022c ; Li et al, 2023 ). AOH showed to lead to the phosphorylation of cAMP response element-binding (CREB) and increased the expression of COX-2 ( Bansal et al, 2019 ).…”
Section: Anticancer Mechanisms and Targeting Signaling Pathways By Al...mentioning
confidence: 99%
“…MAPKs are involved in the phosphorylation of JNK, ERK and p38 which regulate the expression of MSK 1/2 and then p65 ( Xie et al, 2019 ; Garzoli et al, 2022 ; Li et al, 2023 ). Inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) are also key enzymes involved in inflammation and cell stress, being NO an important regulator of COX-2 expression and activity ( Sharifi-Rad et al, 2022c ; Li et al, 2023 ). AOH showed to lead to the phosphorylation of cAMP response element-binding (CREB) and increased the expression of COX-2 ( Bansal et al, 2019 ).…”
Section: Anticancer Mechanisms and Targeting Signaling Pathways By Al...mentioning
confidence: 99%
“…Several studies have reported on BACE1 inhibiting phytochemicals that also bind to and inhibit acetylcholinesterase, another key target in AD [ 52 , 53 , 54 ]. There are arguments that such multi-directed agents may offer unique benefits over single target treatments but here we are specifically interested in what these phytochemicals can yield about the targeting BACE1 [ 55 ]. The goal here is to show that multiple phytochemicals bind to and inhibit the CaMBP BACE1 in support of the primary premise of this review that CaM and its targets are central to the onset and progression of AD and a diversity of phytochemicals exert their AD-related therapeutic effects via them.…”
Section: Bace1 As a Phytochemical Targetmentioning
confidence: 99%
“…Brain functions are influenced by poor nutrition, stress and lack of movement, but also by natural cellular oxidation processes [19,106,[154][155][156][157]. In addition to improving lifestyle, the brain and memory can benefit from the stimulating input of nature due to plants with a beneficial effect on brain functions [158][159][160]. Recent research studied the effects of a Paeonia emodi Wall.…”
Section: Neuroprotectivementioning
confidence: 99%